OPINI PUBLIK TENTANG PEMBERITAAN KASUS CHARLIE HEBDO (Pendapat Ulama Surakarta Tentang Pemberitaan Kasus Charlie Hebdo Di Harian SOLOPOS) - Siswanta, Bagus Adi Muliawan Fauzi, Maya Sekar Wangi & (Transformasi, 2016)
People in their life realize the importance of fulfillment their need toward theinformations, in this case a newspaper as a printing media has an important role. Newspapercan spread out the messages and vary informations to the public. The headline is the maininformation in the newspaper which is interesting to read for the public. One of the cases beingexposed by media is charlie hebdo case about the controversial of caricature and the attackincident.The purpose of the research is to describe the mufti opinions in Surakarta about the caseof charlie hebdo in Solopos daily. This research used different opinion theory by Mellvin D.Defleur and hegemoni theory by Mc. Quail. This method is qualitative descriptive which isdescribing situations, condition, or event. The technique of collecting the data used observationand interview in order to get the accuration. The data analysis used intercative analysis model.This research is among three components, they are : data reduction, data display, andconclusion drawing and verification. The result of the research was known that solopos newsvery influence toward the opinion of the religionist, as the charlie hebdo case. The news aboutthat, begin from the caricature of prophet Muhammad on the cover until the attack which iscaused the victim as in the Solopos daily, make a pro and contra toward public opinion.Keywords: Opinion Public, Charlie Hebdo, Ulama Surakarta